Similarities between Human Immunodeficiency Virus Type 1 and Hepatitis C Virus Genetic and Phenotypic Protease Quasispecies Diversity - Martinez, Miguel Angel (J Virol, 2015)
Human immunodeficiency virus type 1 (HIV-1) and hepatitis C virus (HCV) are two highly variable RNA viruses that cause chronic infections in humans. Although HCV likely preceded the AIDS epidemic by some decades, the global spread of both viruses is a relatively recent event. Nevertheless, HCV global diversity is higher than that of HIV-1. To identify differences in mutant diversity, we compared the HIV-1 protease and HCV NS3 protease quasispecies. Three protease gene quasispecies samples per virus, isolated from a total of six infected patients, were genetically and phenotypically analyzed at high resolution (HIV-1, 308 individual clones; HCV, 299 clones). Single-nucleotide variant frequency did not differ between quasispecies from the two viruses (HIV-1, 2.4 × 10(−3) ± 0.4 × 10(−3); HCV, 2.1 × 10(−3) ± 0.5 × 10(−3)) (P = 0.1680). The proportion of synonymous substitutions to potential synonymous sites was similar (3.667 ± 0.6667 and 2.183 ± 0.9048, respectively) (P = 0.2573), and Shannon's entropy values did not differ between HIV-1 and HCV (0.84 ± 0.02 and 0.83 ± 0.12, respectively) (P = 0.9408). Of note, 65% (HIV-1) and 67% (HCV) of the analyzed enzymes displayed detectable protease activity, suggesting that both proteases have a similar mutational robustness. In both viruses, there was a rugged protease enzymatic activity landscape characterized by a sharp peak, representing the master sequence, surrounded by a collection of diverse variants present at lower frequencies. These results indicate that nucleotide quasispecies diversification during chronic infection is not responsible for the higher worldwide genetic diversity observed in HCV. IMPORTANCE HCV global diversity is higher than that of HIV-1. We asked whether HCV genetic diversification during infection is responsible for the higher worldwide genetic diversity observed in HCV. To this end, we analyzed and compared the genotype and enzymatic activities of HIV-1 and HCV protease quasispecies existing in infected individuals. Our results indicate that HIV-1 and HCV protease quasispecies have very similar genetic diversity and comparable rugged enzymatic activity landscapes. Therapy for HCV has expanded, with new therapeutic agents such as the direct-acting antivirals (DAAs). DAAs, which target HCV NS3 protease and other virus proteins, have improved cure rates. However, major questions remain to be elucidated regarding the virologic correlates of HCV eradication. The findings shown here may help our understanding of the different therapeutic responses observed during chronic HCV infection.